Socialization of the Dangers of Sleeping Late Due to Gaming Addiction: Efforts to Increase Digital Wellness Awareness in Students SMPN 4 Bontolempangan SATAP Ma'Lengu - Arga, Arga; Arba', Muhammad Arkanul; Aulria, Siti Nurhalizah Mutia; Rerung, Charmila Tandi; Rahmatullah, Wahyu; Bana, Suriani (Jurnal Perjuangan dan Pengabdian Masyarakat : JPPM, 2025)
Socialization of the dangers of sleeping late due to gaming addiction at SMPN 4 Bontolempangan SATAP Ma'Lengu aims to increase students' awareness about the negative impact of excessive use of gadgets to play games on sleep quality and overall health. This activity provides a platform for students to understand the concept of digital wellness, recognize the signs of gaming addiction, learn healthy digital time management strategies, understand the importance of sleep hygiene, and develop responsible gadget use habits. Through this socialization, it is hoped that students can reduce excessive gaming time, improve sleep quality, improve academic achievement, and create a healthy balance between digital activities and real life in the school and home environment.